1981
DOI: 10.1007/bf00389743
|View full text |Cite
|
Sign up to set email alerts
|

Peroneal nerve palsy due to fabella

Abstract: In general, the fabella has been considered to have a minor clinical significance, and has not been recognized as one of the causes of peroneal nerve palsy. Seven cases of peroneal nerve palsy due to the fabella are reported. The typical clinical features and the importance of electrophysiological examinations in making an accurate diagnosis are described. Of the seven cases mentioned above, three cases were treated by surgery and four cases by conservative methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 2 publications
1
45
0
Order By: Relevance
“…Surgical intervention for recurrent knee dysfunction associated with this accessory bone has been reported as successful. 4,13,15 A simple manual therapy intervention and subsequent education for effective selfmanagement strategies could significantly reduce the incidence of surgical excision of the fabella. Because the intervention included trial and error in the use of mobilization techniques, the practicing clinician may also need to use this approach in patients with similar case histories.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Surgical intervention for recurrent knee dysfunction associated with this accessory bone has been reported as successful. 4,13,15 A simple manual therapy intervention and subsequent education for effective selfmanagement strategies could significantly reduce the incidence of surgical excision of the fabella. Because the intervention included trial and error in the use of mobilization techniques, the practicing clinician may also need to use this approach in patients with similar case histories.…”
Section: Discussionmentioning
confidence: 99%
“…Common fibular nerve palsies associated with fabella syndrome have been reported in the literature and signs of neurological dysfunction were present in this patient (weakness and atrophy). 6,10,15 There was no evidence of decreased conduction velocity in the common fibular nerve, nor was there evidence of recent denervation of motor units innervated by the common fibular nerve. There was evidence of denervation and reinnervation from a prior insult to motor units within the common fibular nerve distribution.…”
Section: Follow-upmentioning
confidence: 97%
See 2 more Smart Citations
“…(10,11) It has also been suggested that a fabella larger than 10 mm in size requires excision in patients undergoing total knee replacement. (12) However, Weiner and Macnab recommend a six-month period during which conservative management of symptomatic fabellae should be attempted prior to the consideration of surgery for patients with fabella syndrome.…”
Section: Discussionmentioning
confidence: 99%